2021
DOI: 10.1155/2021/5527199
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Outcomes of Perioperative Atrial Fibrillation following Noncardiothoracic Surgery: A Systematic Review and Meta-Regression Analysis of Observational Studies

Abstract: Background. Atrial fibrillation (AF) occurs in 16–30% of patients after cardiac and thoracic surgery and can lead to serious complications like hypoperfusion of vital organs, pulmonary edema, and myocardial infarction. The evidence on risk factors and complications associated with perioperative AF after noncardiothoracic surgery is limited. Methods. The primary objective was to determine demographic and clinical risk factors for new-onset atrial fibrillation associated with noncardiothoracic surgery. A seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Advanced age, male sex, preoperative hypertension, diabetes mellitus, and cardiac disease were identified as important risk factors for perioperative atrial fibrillation. Faced with an aging and comorbid surgical population, the need for risk stratification and close monitoring increases [18].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, male sex, preoperative hypertension, diabetes mellitus, and cardiac disease were identified as important risk factors for perioperative atrial fibrillation. Faced with an aging and comorbid surgical population, the need for risk stratification and close monitoring increases [18].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of POAF after non-thoracic non-cardiac surgery varies widely, from 0.5% to 15%, which reflects the heterogeneity in definitions (inclusion or not of patients with a history of AF), methods used to identify POAF, study populations (geriatric or not) and settings (type of surgeries) [ 4 , 6 , 13 ]. We chose to include in this cohort patients with a history of paroxysmal AF, as for previous cohorts of patients with hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, largely focused on POAF after cardiothoracic surgery, identified factors associated with POAF including baseline characteristics (age, male sex, hypertension, chronic heart failure, ischemic heart disease, chronic kidney disease), and perioperative and postoperative complications (hypovolemia, electrolyte disorders, hypoxemia) [ 4 , 6 , 9 12 ]. However, few data are available regarding POAF after non-cardiothoracic surgery, particularly emergent orthopedic surgery [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the occurrence of POAF in NCS patients was mistakenly perceived as a relatively benign complication, primarily due to its self-limiting nature and asymptomatic presentation. However, recent investigations have illuminated the detrimental impact of POAF, which encompasses hemodynamic instability, prolonged hospitalization, infectious complications, pulmonary complications, heightened risk of stroke, elevated inhospital mortality rates, and escalated healthcare expenditures (2, [6][7][8].…”
Section: Introductionmentioning
confidence: 99%